Sex and age differences in sexual attitudes and dispositional sexual motives among individuals in early adulthood - Grod, Janet V. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
This article presents the results of the study of sex and age differences in sexual attitudes and dispositional sexual motives among individuals in periods of early adulthood. The significance of human sexuality issues, in particular sexual attitudes and motives, is revealed. The methodological approach to the study of sexual attitudes and dispositional sexual motives, a questionnaire of sexual attitudes and a questionnaire of affective motivational orientations in sexual life are described. The indicators of sexual attitudes and dispositional sexual motives in women and men in the initial and late periods of early adulthood were determined. It was revealed that there are both sex and age differences in sexual attitudes and dispositional sexual motives in individuals. Thus, the study of human sexual attitudes and motives can lead to a better understanding of the way they influence sexual actions, as well as to the prediction of sexual behaviour.